SALENG ABENTHO: A STRATEGY TO REDUCE COSTS OF LOCAL RESOURCES-BASED MADURESE CORN FARMING - Lubis, Hisnuddin; Rohmatillah, Nely (Jurnal Ilmu Sosial dan Humaniora, 2021)
Madurese corn is one of the leading agricultural commodities of Madura. Its opportunity is quite prospective, given that the national corn-based industry shows a positive trend from year to year. The problem is that the corn cultivation by the Madurese people is merely oriented to serving the purpose of meeting food needs rather than a profit-oriented one. This is because the planting costs are relatively expensive with a thin profit margin. Therefore, a cost-efficient strategy for local resources-based Madurese Corn Farming is required. The present study is expected to produce a strategic model for using local resources to reduce the costs of Madurese corn farming. This study was carried out in Gapurana Village, Kalianget Sub-district of Sumenep Regency Madura, using the qualitative descriptive approach. Data were collected by observation and in-depth interviews and analyzed using the Mils and Huberman model. The results showed that local resources, especially social resources in the form of solidarity ‘saleng abentho’, effectively reduced the costs of Madurese corn farming. This resource could be managed and institutionalized by involving farmer groups and policies to realize an industrial-scale Madurese Corn Farming.